Sca-1 is negatively regulated by TGF-β1 in myogenic cells - Long, Kimberly K. (Federation of American Societies for Experimental Biology, 2011)
Sca-1 (stem cell antigen-1) is a member of the Ly-6 family of proteins and regulates cell proliferation, differentiation, and self-renewal in multiple tissues. In skeletal muscle, Sca-1 inhibits both proliferation and differentiation of myogenic cells. Sca-1 expression is dynamically regulated during muscle regeneration, and mice lacking Sca-1 display increased fibrosis following muscle injury. Here, we show that Sca-1 expression is negatively regulated by TGF-β1 and that this inhibition is dependent on Smad3. We demonstrate that levels of TGF-β1 in skeletal muscle rapidly increase on injury and that the majority of this TGFβ1 is produced by infiltrating macrophages. Sca-1 is expressed in multiple cell types, and we demonstrate that TGF-β1 represses Sca-1 expression in T cells and other immune cell populations derived from the spleen, indicating that regulation by TGF-β1 is a general feature of Sca-1 expression in multiple cell types. Elucidation of the mechanisms by which Sca-1 expression is regulated may aid in the understanding of muscle homeostasis, potentially identifying novel therapeutic targets for muscle diseases.—Long, K., Montano, M., Pavlath, G. K. Sca-1 is negatively regulated by TGF-β1 in myogenic cells.